PENGARUH STRUKTUR MODAL, KEBIJAKAN HUTANG, DAN INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK - Amelia Budiani (Yayasan Kayyis Mulia Jaya, 2026)
The study aims to analyze the effect of Capital Structure, Debt Policy, and Inventory Intensity on Tax Avoidance. The type of research employed is quantitative, with data sourced from secondary materials. The sample was determined using purposive sampling, resulting in 30 companies selected based on the criteria of being listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Data were obtained from the IDX and subsequently processed and analyzed using panel data regression with EViews version 12. The findings indicate that capital structure, debt policy, and inventory intensity simultaneously influence tax avoidance. Partially, capital structure has a significant effect on tax avoidance, while debt policy and inventory intensity do not significantly affect tax avoidance. Keywords: Capital Structure, Debt Policy, Inventory Intensity, Tax Avoidance